Mandatory Housing Contributions and Non Housing Consumption among Urban Nigerian Households - Chiamaka Grace Okafor; Ngozi Esther Nwankwo; Blessing Amarachi Eze; Aisha Fatima Bello (Journal of Economics Business Industry, 2025)
This study investigates the causal effect of mandatory National Housing Fund (NHF) contributions on non-housing consumption patterns among urban Nigerian households. Drawing on cross-sectional data from the 2023/24 Nigeria General Household Survey-Panel Wave 5 (GHS-Panel), we employ instrumental variable estimation to address endogeneity arising from reverse causality and omitted variable bias. Findings reveal a statistically significant negative relationship between NHF contributions and discretionary spending: an NGN 1 increase in per capita NHF outlays corresponds to an NGN 0.921 decline in non-housing consumption at the state level. This crowd-out effect intensifies among households that refrain from utilizing NHF for residential mortgage purposes, exhibiting a marginal propensity to consume reduction of NGN 1.872 per naira contributed. Heterogeneity analyses further demonstrate that low-income households, who exhibit lower NHF withdrawal probabilities, bear the inhibitory burden most acutely. Their non-housing expenditures decline more sharply relative to higher-income counterparts under equivalent contribution levels. Results from both the theoretical and empirical models suggest that whether a household participates in the NHF matters, but it is far more consequential for the household to actively leverage its lending capacity to relax liquidity constraints rather than merely sustain participation without accessing loans.